The Ides of April - Davis, Lindsey (Davis, Lindsey. Flavia Albia mystery., 2013)
Working as a private informer in Rome during the reign of Domitian, Flavia Albia is hired to investigate a fatal accident, an investigation that turns sinister when her client dies under suspicious circumstances that place Flavia's reputation at stake.